KORELASI KADAR ASAM URAT DALAM DARAH DAN KRISTAL ASAM URAT DALAM URINE - Naid, Tadjuddin; Mas'ud, Ita Ayuningsih; Haryono, Kus (Fakultas Farmasi UMI, 2014)
The study had been done about the correlation test betweenblood uric acid level, and urine uric acid cristal. The objective of this study was to find the correlation betweenblood uric acid level, and urine uric acid cristal. This studywas an observational study with cross sectional approach using serum and urine samples were taken from patients who have met the criteria of the study sample. The samples number are36 that all of them analyzed with test blood uric acid, and urine uric acid cristal.The data of result was processed and analyzed with statistic test of correlation test. The results of study showed that there are correlation between blood uric acid level and urine urine uric acid, that the more uric acid cristal exrated viaurine will make to reduce blood uric acid level.